Risk of psychiatric disorders following trigeminal neuralgia: a nationwide population-based retrospective cohort study - Wu, Tung-Han (J Headache Pain, 2015)
BACKGROUND: TN is one of the most common causes of facial pain. A higher prevalence of psychiatric co-morbidities, especially depressive disorder, has been proven in patients with TN; however, a clear temporal-causal relationship between TN and specific psychiatric disorders has not been well established. We performed a nationwide population-based retrospective cohort study to explore the relationship between TN and the subsequent development of psychiatric disorders, including schizophrenia, bipolar disorder, depressive disorder, anxiety disorder, and sleep disorder. METHODS: We identified subjects who were newly diagnosed with TN between January 1, 2000 and December 31, 2010 in the Taiwan National Health Insurance Research Database. A comparison cohort was constructed for patients without TN who were matched according to age and sex. All TN and control patients were observed until diagnosed with psychiatric disorders, death, withdrawal from the National Health Institute system, or until December 31, 2010. RESULTS: The TN cohort consisted of 3273 patients, and the comparison cohort consisted of 13,092 matched control patients without TN. The adjusted hazard ratio (aHR) of depressive disorder, anxiety disorder and sleep disorder in subjects with TN was higher than that of the controls during the follow-up [aHR: 2.85 (95 % confidence interval: 2.11–3.85), aHR: 2.98 (95 % confidence interval: 2.12–4.18) and aHR: 2.17 (95 % confidence interval: 1.48–3.19), respectively]. CONCLUSIONS: TN might increase the risk of subsequent newly diagnosed depressive disorder, anxiety disorder, and sleep disorder, but not schizophrenia or bipolar disorder. Additional prospective studies are required to confirm these findings.